2015
DOI: 10.17221/58/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of red wines in Southeast Turkey

Abstract: Değİrmencİ Karataş D., Aydin F., Aydin I., Karataş H. (2015): Elemental composition of red wines in Southeast Turkey. Czech J. Food Sci., 33: 228-236.Mineral profiles of wines and soil extracts were analysed in the five most popular international wines (Cabernet Sauvignon, Syrah, Merlot, Cot, and Tannat) and national Boğazkere, which is one of the highest-quality grapevine varieties grown in Turkey. We carried out study to establish the mineral and metal concentrations in wines from Southeast Anatolia of Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It should be noted that Zn is a trace element naturally found in soil. For this reason, Zn plays a key role in the growth of plants [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that Zn is a trace element naturally found in soil. For this reason, Zn plays a key role in the growth of plants [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jackson et al [42] reported a significant and positive correlation between both pH and color and overall wine quality. The importance of TDS, EC, and salt measurements rely on the fact that these are an approach to minerals content [45], which are important in wine quality, as the minerals present in wine have been related to those present in the soil, and these have been associated with the wine's nutritional composition and safety [46].…”
Section: Discussionmentioning
confidence: 99%
“…The official methods for the determination of metals in wine, commonly applied in routine laboratories, are based on atomic spectrometry, 3,7,8 including flame atomic absorption spectrometry (FAAS), 3,[7][8][9][10][11][12][13][14] graphite furnace atomic absorption spectrometry (GFAAS), 3,7,8,15,16 inductively coupled plasma optical emission spectrometry (ICP-OES), 3,7,8,[17][18][19][20][21][22] and inductively coupled plasma mass spectrometry (ICP-MS), 3,5,7,8,17,[23][24][25][26][27][28][29][30][31] being the latter the most applied technique in recent years. However, the introduction of organic samples into the plasma source is still a challenge as ICP techniques suffer from severe interferences caused by complex organic matrices, including matrix effects, plasma degradation and soot deposition at the injector tip and interface cones.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of organic samples into the plasma source is still a challenge as ICP techniques suffer from severe interferences caused by complex organic matrices, including matrix effects, plasma degradation and soot deposition at the injector tip and interface cones. 32,33,34 To circumvent them, several sample preparation approaches have been developed, such as sample dilution, 7,22,35,36,37,38,39,40,41 conventional dry/wet sample digestion, 7,36,42 microwave-or ultraviolet-assisted acid digestion, 7,10,19,22,43,44,45 dealcoholisation 7,42 and analyte separation. 7 However, all these methods show some problems caused by the addition of reagents, potential sample contamination and degradation of limits of detection, among others.…”
Section: Introductionmentioning
confidence: 99%